Wilderness and Waterpower How Banff National Park Became a Hydroelectric Storage Reservoir - Nelles, H. V.; Armstrong, Christopher (Energy, Ecology, and the Environment, 2013)
This engaging book explores how the need for electricity at the turn of the century affected and shaped Banff National Park. Today's conservationists and energy researchers will find much to think about in this tale of Alberta's early need for electricity, entrepreneurial greed, debates over aboriginal ownership of the river, moving park boundaries to accommodate hydro-electric initiatives, the importance of water for tourism, rural electrification, and the ultimate diversion to coal-produced electricity. It is also a lively national story, involving the irrepressible and impetuous Max Aitkin (later Lord Beaverbook), R.B. Bennett (local legal advisor and later prime minister), and a series of local politicians and bureaucrats whose contributions confuse and conflate issues along the way.